2016
DOI: 10.15244/pjoes/60858
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Bioavailability of Metals in Soils on Oil Palm Plantations in Nigeria

Abstract: We investigated the speciation, bioavailability, and mobility of metals in soils from selected states on oil palm plantations in southwest Nigeria. Soils were analysed for total metal content and speciation on all sampling locations. Metal concentrations were compared against pH, electrical conductivity (EC) and soil organic matter (SOM), which were high at all the sampling locations. The speciation results deduced that the concentrations of the different fractions vary widely at each sampling location. Cd is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 49 publications
2
10
0
5
Order By: Relevance
“…Similar studies on soils sampled on the oil plantations have shown that lead is a potentially mobile element and soluble in soil water and under acidic conditions of the soil, it becomes mobile and can bio-accumulate in the palm fruit (Yasmin et al, 2000;Olafisoye et al, 2013;Olafisoye et al, 2014). A recent study on the bioavailability and accessibility of metallic elements in the soil on the oil palm plantations revealed the environmental quality of manganese in soil solution (Olafisoye et al, 2016). This shows that Manganese is bound in loose forms of precipitates to organic matter and clays in the speciation studies in the soil of the oil plantation under investigation.…”
Section: Analysis Of Real Samplesmentioning
confidence: 90%
“…Similar studies on soils sampled on the oil plantations have shown that lead is a potentially mobile element and soluble in soil water and under acidic conditions of the soil, it becomes mobile and can bio-accumulate in the palm fruit (Yasmin et al, 2000;Olafisoye et al, 2013;Olafisoye et al, 2014). A recent study on the bioavailability and accessibility of metallic elements in the soil on the oil palm plantations revealed the environmental quality of manganese in soil solution (Olafisoye et al, 2016). This shows that Manganese is bound in loose forms of precipitates to organic matter and clays in the speciation studies in the soil of the oil plantation under investigation.…”
Section: Analysis Of Real Samplesmentioning
confidence: 90%
“…Bahan organik tanah dianggap sebagai elektron donor yang menyumbang reaksi reduksi logamlogam pada pH rendah (Olafisoye et al, 2016).…”
Section: Kandungan Haraunclassified
“…Kandungan Zn pada jenis tanah ini lebih rendah dibandingkan kandungan Zn pada tanah di Malaysia, yaitu sekitar 95 ppm (Zarcinas et al, 2004). Batas maksimum diperbolehkannya kandungan Zn dalam tanah adalah 90 ppm (Olafisoye et al, 2016). Kandungan Zn dalam tanah dapat berasal dari bahan induk, dekomposisi bahan organik, dan pupuk, pengotor pada pupuk RP yang sudah diaplikasikan selama empat tahun.…”
Section: Kandungan Haraunclassified
See 2 more Smart Citations